The Impact of CAFTA Agreement on Trade, Challenge and Opportunities - Masyhuri (Journal of World Trade Studies, 2010)
Main CAFTA (China ASEAN Free Trade area) has been started on 1 January 2010. The full CAFTA will be realized in 2015. It has political and economical motives. The free trade area is the world largest in term of population and the third largest in term of GDP (Gross Domestic Product). This paper discusses the theoretical and possible impact of CAFTA on trade articularly in Indonesia. Some products will be exported and imported more. This will increase production of some products and decrease production of some other products. The final benefit results will be depended on the readiness of the country. Therefore there are suggestions to dig more benefit and to prevent losses. The promotion of some product, the protection of domestic production and increase the competitiveness of the country should be done.